Behavioral Change Study of Catla-Catla During Exposure of Mercury & Zinc - S. S. Chandanshive (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
The present study of small change in fish behavior in 0.03 mg/L mercury may be the avoidance behavior of the animal to metal. Fish exposed to concentrations of metal do not reach the stage of exhaustion, rather they accommodate and adapt to the stressor. Increase in swimming activity with increased breathing rate, lethargic condition and loss of equilibrium in Catla Catla exposed to mercury (0.06 and 0.12 mg/L and zinc (3.0 and 7.0 mg/L) are attributed probably to the disturbances in the metabolic reactions resulting in the depletion of energy. It is possible that animals which have higher metabolic activity could require higher levels of oxygen and thus would have a higher respiration or breathing rate. The lowest treatment of mercury (0.03 mg/L) caused little change in fish behavior, which may be the avoidance behavior of animals to pollutants in the receiving water. A significant response to 0.06 mg Cu/l was noted: the swimming activity and breathing rate of the fish increased. In the highest treatment (0.12 mg cu/l) fish became lethargic and lost equilibrium. Zinc, at the lowest treatment (0.5 mg/L), did not cause any visible change in fish behavior. However, in 3.0 mg an/l, the fish tended to swim faster and showed an increased breathing rate. In the highest treatment of zinc (7.0 mg Zn/L), the fish showed a lethargic response and lost equilibrium (Table 2). It is evident from the observed behavioral changes in Catla Catla that both heavy metals have the same pattern of effects.